Association between Blood Lead, Nutritional Status, and Risk Factors of Hypertension and Diabetes Mellitus: A Study in Female Traffic Police Officers in Yogyakarta - Sudargo, Toto; Fathsidni, Banun Ma’rifah; Zakia, Dea Farah; Rachmawati, Yuliana Novita; Hariawan, Muhammad Hafizh; Muslichah, Rahadyana; Paramastri, Rathi (Jurnal Gizi dan Pangan, 2018)
The research aimed to investigate the association of nutritional status, blood lead level, and risk factors of hypertension and diabetes mellitus in female traffic police officers routinely exposed to lead in Yogyakarta, Indonesia. Fifty-four female traffic police officers aged 20-50 year old participated in this cross-sectional study. As risk factors of diabetes and hypertension, Body Mass Index (BMI) was calculated from height and weight data while percentage of body fat (%BF) was measured using Bioelectrical Impedance Analysis (BIA). Energy intake (EI) was assessed using 1x24-hour dietary recall. Atomic Absorption Spectrophotometer (AAS) method was conducted to measure blood lead (Pb-S). Blood pressure (BP) was measured using mercury sphygmomanometer while blood glucose (Glu) was measured in laboratory. Pearson’s and Spearman Rank correlation test were performed for statistical analysis. We demonstrated that Pb-S was positively correlated with both systolic and diastolic BP but not with BMI, %BF, and Glu. Meanwhile, there was a correlation between Glu and either BMI or %BF but not EI. Therefore, our study indicates that exposure to lead is correlated with hypertension while nutritional status is more correlated with diabetes mellitus.